2022
DOI: 10.1155/2022/7606949
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Examination of the Sexting Motives and Attitudes: Bosnia and Herzegovina vs. Croatia

Abstract: Many sexting studies conducted in the Western cultures have shown that the percentage is higher in less traditional cultures. However, the generalizability of this phenomenon to non-Western cultures has not been extensively researched. The purpose of this study is to examine and explain cross-cultural differences in sexting behavior among subjects from Bosnia and Herzegovina and Croatia. A mixed methods approach was used. The first, qualitative phase included focus groups with two groups of high school student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Further research should be primarily focused on exploring consensual and nonconsensual sexting as different forms of sexting. Also, some authors suggest operationalizing and measuring sexting behavior as a continuum from consensual to non-consensual (Dodaj et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research should be primarily focused on exploring consensual and nonconsensual sexting as different forms of sexting. Also, some authors suggest operationalizing and measuring sexting behavior as a continuum from consensual to non-consensual (Dodaj et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have investigated the determinants of sexting have mainly focused on individual factors, with individual differences in gender, age, attitudes, peers, and intimate context being particularly important for sexting engagement. There is a growing body of literature on youth sexting in Western cultures (Dodaj, Sesar, & Novak, 2022;Jerome & Srinivasan, 2014), and a small number of studies examined cross-cultural differences in the predictors of this behavior (Gassó Moser et al, 2021). Although rarely studied, contextual factors (such as cultural or societal values) could also play an important role in the motivation and engagement of youth in some forms of sexting behavior .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the TPB was able to predict sexting behavior in different cultures and across different age groups, including in the United States, Asia, South Africa, and the United Kingdom, as well as among adolescents and young adults. Given the lack of sexting studies in the south-eastern regions of Europe (see Dodaj et al, 2022) and among emerging adults, it appeared to be useful to explore sexting intention in Croatia and Bosnia and Herzegovina. Furthermore, as a sexting is understood as a cultural phenomenon shaped by cultural norms and value systems that determine how individuals interact with each other in this aspect of sexual behaviour, TPB seems as useful theoretical framework for understanding sexting behaviour (Crofts et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because Croatian and Bosnian-Herzegovinian populations are more traditional cultures associated with repressive sexuality, including sexting practices, compared to other parts of Western Europe (Dodaj et al, 2022), their own beliefs and desire to explore sexuality through sexting may differ. In addition, we must take into account that emerging adulthood in the southern parts of Europe, which were examined for this study, looks somewhat different or has cultural characteristics than in other parts of Europe.…”
Section: Introductionmentioning
confidence: 99%